Teaching English Grammar to Young Learners Through Clil Method (Texas Journal of Philology, Culture and History, 2023)
This paper purposes to describe importance of teaching grammar in English classes as important as other skills, additionally focuses on CLIL method and its implementation while teaching grammar in primary classes. The research was dedicated to gather teachers’ attitude and preferences to use CLIL method in educating grammar in primary classes.